ICT outreach for farmers and other stakeholders to enhance productivity of oilseeds: ICT outreach for farmers and other stakeholders to enhance productivity of oilseeds - SAMALA AKHILA; N MAMATHA; K AKHILA (Journal of Oilseeds Research, 2020)
Oilseeds are very important next to food-grains in India, in terms of acreage, production and value. Edible oilplays an important role in nutrition since, it acts as a carrier for fat soluble vitamins in the body as well as otherphysiological functions in the body. Therefore, there is an urgent need to increase the productivity of oilseeds in order to meet the daily requirements. Information and communication technology (ICT) could be a possible solution which can share timely and accurate information on weather, inputs, markets, and prices, by feeding information into research and development initiatives, by disseminating knowledge to farmers, by connecting producers and consumers, and through many other avenues. The research efforts of schemes and mobile apps on oilseeds under ICAR has resulted in widespread network in development of high yielding varieties/hybrids coupled with the location-specific crop production and protection technologies. This paper deals with importance of ICT outreach for farmers and other stakeholders that increases production of oilseed crops and reduction of oil imports.